Rancang Bangun Sistem Manajemen Pengelolaan Data Tenant Mall Berbasis Website di PT. Artisan Wahyu - Ari Adrian; Ahmad Fikri Zulfikar (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
The growing trend of information technology and a shift in habit that avoid face-to-face meeting encourage research that produces a new step in transactions and negotiations so that it does not require too many processes that require the perpetrators to meet in person. For those reasons, this new tenant rental system is built. By using the Waterfall Method, this study focuses on the final goal, which is to create a new system that will facilitate the work and make it easier for the actors involved in it. In addition, this method also has a clearer working sequence. This tenant rental system uses a web base that can be easily accessed anywhere and anytime so that transactions can be carried out and completed more easily. Keywords : Data Management System, Tenant Rent.